Spectrum Sharing Policy: Interoperable Communication and Information Sharing for Public Safety. Issue 1 (7th November 2017) - Kapucu, Naim; Haupt, Brittany; Yuksel, Murat
Abstract : Among Public Safety Communication (PSC) systems there is a mounting concern over interoperability. To mitigate such interoperability issues, the Department of Homeland Security (DHS) created the National Emergency Communications Plan (NECP) to guide the implementation of a nationwide PSC system; however, this system hinges on the effective integration of heterogeneous wireless communication systems, efficient spectrum sharing, and ability to overcome other key policy or management obstacles. To explore these topics further, this paper reviews government documents pertaining to interoperability, wireless communication, and spectrum sharing. Within the context of PSC, the study aims to identify key obstacles; understand how government documents address policies and regulations related to the wireless communication, interoperability, and spectrum sharing; and, determine how to address overload of wireless communication and spectrum during a major disaster situation.